Color Scheme Authentication for Session Password (International Journal of Engineering and Computer Science, 2017)
In this paper we are dealing with the new scheme to provide authentication for files and folders using colours in which the password are generated for every session, that is we have our new password every time you login hence we called it as color scheme authentication for session password. The main purpose for this method is to stricter the authentication, to provide security to our documents in folders and PDF. We have implemented and it proved to be a better technique in providing authentication when compared to textual passwords and other existing techniques.